Voluntary Exercise Prevents Hypertensive Response Sensitization Induced by Angiotensin II - Xue, Baojian; Cui, Jun-Ling; Guo, Fang; Beltz, Terry G.; Zhao, Zi-Gang; Zhang, Geng-Shen; Johnson, Alan Kim (Frontiers in Neuroscience, 2022)
Exercise training has profound effects on the renin-angiotensin system, inﬂammatory cytokines and oxidative stress, all of which influence autonomic nervous system activity and regulate cardiovascular function in both physiological and pathophysiological states. Using an Induction-Delay-Expression paradigm, our previous studies demonstrated that various challenges (stressors) during Induction resulted in hypertensive response sensitization (HTRS) during Expression. The present study tested whether voluntary exercise would protect against subpressor angiotensin (ANG) II-induced HTRS in rats. Adult male rats were given access to either “blocked” (sedentary rats) or functional running (exercised rats) wheels for 12 weeks, and the Induction-Delay-Expression paradigm was applied for the rats during the last 4 weeks. A subpressor dose of ANG II given during Induction produced an enhanced hypertensive response to a pressor dose of ANG II given during Expression in sedentary rats in comparison to sedentary animals that received saline (vehicle control) during Induction. Voluntary exercise did not attenuate the pressor dose of ANG II-induced hypertension but prevented the induction of HTRS seen in sedentary animals. Moreover, voluntary exercise reduced body weight gain and feed efficiency, abolished the augmented blood pressure (BP) reduction after ganglionic blockade, reversed the increased mRNA expression of several pro-hypertensive components, and upregulated mRNA expression of several antihypertensive components in the lamina terminalis and hypothalamic paraventricular nucleus, two key brain nuclei involved in sympathetic activity and BP regulation. These results indicate that exercise training plays a beneficial role in preventing HTRS and that this is associated with shifting the balance of the brain prohypertensive and antihypertensive pathways in favor of attenuated central activity driving sympathetic outflow and reduced BP.